HIV/AIDS and climate in food security crises :a study of Southern Africa, 2001-2005. - Van Riet, Gideon (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Political Science.International Studies))--University of Stellenbosch, 2006.